The Effect of Education Level on Income Inequality: Empirical Evidence from Indonesia, 2015 – 2023 - Haryono, Aulia Hammidah; Widodo, Wahyu (CV ODIS, 2025)
This study examines the effect of education on income inequality in Indonesia using panel data from 34 provinces over the period 2015-2023. The study investigates four main variables: average years of schooling, gross enrollment rate on tertiary education, government expenditure on education, and Gross Domestic Regional Product (GDRP) per capita. Applying a Fixed Effects Model with Least Square Dummy Variable (LSDV) approach, the findings indicate the longer average years of schooling are significantly associated with a reduction in income inequality. Government spending on education also reveals that greater expenditure leads to lower income inequality, reinforcing the role of public investment in promoting equity. Otherwise, an increase in the gross tertiary enrollment rate alone is insufficient to reduce income inequality unless accompanied by improvements in quality and access to education, and thus does not have a significant effect. GDRP per capita demonstrates a negative and significant relationship with income inequality, consistent with Kuznets’ theory that redistribution is supported by economic development at certain stages. The study emphasizes that to address the persistent regional income disparities in Indonesia, focused education policies and inclusive growth strategies are required.